From Leadership to Learning: Examining the Managerial Influence of School Principals on Teacher Effectiveness - Thaha, Hijaz; Pirol, Abdul; Guntur, Muhammad (International Journal of Asian Education, 2025)
This study investigates the influence of school principals’ managerial competence on teacher instructional effectiveness in a religious-based secondary school (madrasah) in Indonesia. Managerial competence is conceptualized across three core dimensions: conceptual skills (strategic planning), human skills (interpersonal relations and motivation), and technical skills (administrative and instructional support). Employing a quantitative ex post facto design, data were collected from 16 teachers using structured questionnaires, non-intrusive observations, and document analysis. Linear regression analysis revealed a significant and positive relationship between principals’ managerial competence and teacher effectiveness (R² = 0.457, p = 0.002), with both variables rated in the "very high" category. The findings support transformational and instructional leadership theories and emphasize the strategic role of managerial competence in enhancing teaching quality. This study contributes practical insights for educational policymakers and leadership development programs, particularly in resource-constrained school environments. However, limitations related to sample size and self-reporting suggest caution in generalizing the results. Future research should examine additional factors influencing teacher performance to build a more comprehensive model. This study provides a novel, component-based analysis of leadership influence in religious-based schools, an area rarely addressed in leadership literature.